O que é a neuroantropologia afinal? Considerações e contribuições de uma ciência pouco conhecida - da Costa, Otávio Barduzzi Rodrigues [UNESP] (Universidade Federal de Sao Paulo, 2014)
This paper intends to explain the contributions of Neuro-anthropology. In this work, will be propose some data and conjectures of Neuroanthropology, that it is not much representative in Brazil, or in the hole world. Although exists the Neuro-Anthropology International Society, and it is a science that can cooperate to the growth of neuroscience, it can clarify some matters relating to this multidisciplinary science and provide certain medical explanations of cognitive disorders. The purpose of this articleisnot to exhaust the topic,it is just to show the possible contributions of Neuro-Anthropologythat is still incipient in the fields of neuroscience.
What is neuroanthropology? Considerations and contributes of an poorly known science
Keywords: Anthropology; Cognitive science; Neuroscience